The restoration of Fernando VII in 1814 - La Parra López, Emilio (2021)
This study provides an explanation about the political change in 1814 Spain. Unlike from the Bourbons restoration in France and Naples, the return to traditional Monarchy in Spain was not due to an agreement between the political forces of the country. Neither was a "natural fact" due to the lack of support of the constitutional system by Spaniards, as some historians have said. The political change was the result of a violent imposition though a coup of state from the counter-revolutionary sector, which used the good public opinion about Fernando VII and had the support of Napoleon as well as Wellington and the British government by different issues.